Mathematiklernen mit digitalen Schulbüchern im Spannungsfeld zwischen Individualisierung und Kooperation - Rezat, Sebastian (Mobile Medien im Schulkontext)

Rekonstruktion diagrammatischen Schließens am Beispiel der Subtraktion negativer Zahlen - Schumacher, Jan (Beiträge zum Mathematikunterricht 2019)

A Hypothetical Learning Trajectory for the Learning of the Rules for Manipulating Integers - Schumacher, Jan; Rezat, Sebastian (Proceedings of the Eleventh Congress of the European Society for Research in Mathematics Education (CERME11, February 6 – 10, 2019))
In this paper, we first outline a Hypothetical Learning Trajectory (HLT), which aims at a formal understanding of the rules for manipulating integers. The HLT is based on task formats, which promote algebraic thinking in terms of generalizing rules from the analysis of patterns and should be familiar to students from their mathematics education experiences in elementary school. Second, we analyze two students' actual learning process based on Peircean semiotics. The analysis shows that the actual learning process diverges from the hypothesized learning process in that the students do not relate the different levels of the diagrams in a way that allows them to extrapolate the rule for the subtraction of negative numbers. Based on this finding, we point out consequences for the design of the tasks.
Keywords: diagrammatic reasoning; hypothetical learning trajectory; induction extrapolatory method; integers; negative numbers; permanence principle; semiotics

Proceedings of the Third International Conference on Mathematics Textbook Research and Development: 16-19 September 2019 Paderborn, Germany

Mathilde Vaerting. Deutschlands erste Mathematikdidaktikderin - Werth, Gerda (Beiträge zum Mathematikunterricht)

„...weil man Fermi-Aufgaben so rechnet“. Modelltexte als sprachliche Ressource für das Erklären von Lösungswegen bei Fermi-Aufgaben - Rezat, Sara; Rezat, Sebastian (In: Mathematik differenziert 3/2019)

An Introduction to Grounded Theory with a Special Focus on Axial Coding and the Coding Paradigm - Vollstedt, Maike; Rezat, Sebastian (Compendium for Early Career Researchers in Mathematics Education)

Semiotische Analyse von Sinnkonstruktionsprozessen bei einem innermathematischen Zugang zum Erlernen negativer Zahlen - Schumacher, Jan (Beiträge zum Mathematikunterricht 2018)

Present Research on Mathematics Textbooks and Teachers’ Resources in ICME-13: Conclusion and Perspectives - Rezat, Sebastian; Visnovska, Jana; Trouche, Luc; Qi, Chunxia; Fan, Lianghuo (Research on Mathematics Textbooks and Teachers’ Resources: Advances and Issues)

Textaufgaben verstehen. Lesen und Variieren komplexer Textaufgaben mit sprachlich-mathematischen Strategien. - Topalović, Elvira; Kuzminykh, Ksenia; Rezat, Sebastian (In: mathematik lehren)

Examining peer-interaction during individual work with a digital textbook in a primary mathematics classroom - Rezat, Sebastian; Häsel-Weide, Uta (PROCEEDINGS of the fith ERME TOPIC CONFERENCE (ETC 5) on Mathematics Education in the Digital Age (MEDA))

Sinnkonstruktion beim Erkunden von Mustern und Strukturen - Schumacher, Jan (Beiträge zum Mathematikunterricht 2017)

Subject specific genres and genre awareness in integrated mathematics and language teaching - Rezat, Sara; Rezat, Sebastian (EURASIA Journal of Mathematics, Science & Technology Education 13 (7b))

Erkunden mathematischer Strukturen anstatt Interpretation in Modellen – Ein innermathematischer Zugang zu negativen Zahlen - Schumacher, Jan (Beiträge zum Mathematikunterricht 2016)

Sprachsensibler Umgang mit Textmustern im Mathematikunterricht am Beispiel von Konstruktionsbeschreibungen - Rezat, Sara; Rezat, Sebastian; Janzen, Sabrina (Beiträge zum Mathematikunterricht 2015. Vorträge auf der 49. Tagung für Didaktik der Mathematik vom 09.02.2015 bis 13.02.2015 in Basel. Band 2)

Mathematische Sachaufgaben verstehen und erklären - Rezat, Sara; Rezat, Sebastian (Praxis Deutsch 233)